Catalytic fast pyrolysis of corn stover in a fluidized bed heated by hot flue gas: Physicochemical properties of bio-oil and its application - Wen, Yang; Peng, Fu; Weiming, Yi (International Journal of Agricultural and Biological Engineering, 2017)
Fast pyrolysis of corn stover was performed at temperatures in the range of 450°C-525°C in a fluidized bed. The chemical composition of the bio-oil acquired was analyzed by GC/MS, and its pH, kinetic viscosity and calorific values were determined. In the pyrolysis system used in this experiment, some improvements to former pyrolysis systems were done. Two screw feeders were used to prevent jamming the feeding system, and the condenser was equipped with some nozzles and a heat exchanger to cool quickly the cleaned hot gas into bio-oil. The results showed that the bio-oil yield increased with increasing pyrolysis temperature and then declined with a further increase in pyrolysis temperature. The highest bio-oil yield of 43.3 wt.% was obtained at 500°C with the dolomite as bed material. The char yield always decreased with the increase of temperature. The major chemical compounds of bio-oil included acetol, butanone, acetic acid, propionic acid, ethylene glycol, phenol, etc. Pyrolysis oil was completely immiscible in diesel, but homogeneous emulsions were obtained when mixing the pyrolysis oil, emulsifier with diesel in different ratios.Keywords: corn stover, pyrolysis, bio-oil, fluidized bed, hot flue gas, GC/MSDOI: 10.25165/j.ijabe.20171005.2473Citation: Yang W, Fu P, Yi W M. Catalytic fast pyrolysis of corn stover in a fluidized bed heated by hot flue gas: Physicochemical properties of bio-oil and its application. Int J Agric & Biol Eng, 2017; 10(5): 226–233.